Exploring participant perspectives through semi-structured interviews: A case study of interactive comic development - Fadhlan Muchlas Abrori; Risma Fazira; Rusmir Hosic (Research and Development in Education (RaDEn), 2026)
Background-Quantitative approach in the development phase of learning media development research in Indonesia is more popular than qualitative. Objectives-This study introduces a qualitative approach as an alternative way to gather participants' perspectives on interactive comics development. Method-was a semi-structured interview, focuses on three aspects: content, visual, and interactivity. Data analysis used thematic analysis based on interview transcripts. Results-Content-related themes are related to positive participant responses to a simple storyline and content accessibility to broader audiences. To ensure the reliability of the themes, intercoder agreement was also calculated, with results indicating the level of agreement between coders regarding the codes mapped from the transcripts. Visual themes include participant perspectives about improvements in the cover part, typing, and readability. Interactivity-related themes focus on adding interactive content through quizzes with a higher level of complexity. The results of this study provide an overview that the insight of participants through a qualitative approach is richer because participants offer in-depth insight into the media. Conclusions-Although this study has limitations, such as the number of participants and a high level of subjectivity due to the qualitative approach, this can be improved in future research by diversifying the participants involved.